Mechanochemical borylation of aryldiazonium salts; merging light and ball milling - Hernández, José G. (Beilstein Journal of Organic Chemistry, 2017)
Merging of photo- and mechanochemical activation permitted studying the role of eosin Y in the borylation of aryldiazonium salts in a ball mill. Simultaneous neat grinding/irradiation of the reactants and the photocatalyst led to the formation of boronates in a molten state. On the other hand, the catalyst-free liquid-assisted grinding/irradiation reaction also led to product formation, featuring a direct photolysis pathway facilitated by substrate–solvent charge-transfer complex formation.
Keywords: aryldiazonium salts; borylation; eosin Y; mechanochemistry; photocatalysis